Beyond Arabidopsis: Differential UV-B Response Mediated by UVR8 in Diverse Species - Tossi, Vanesa Eleonora; Regalado, Jose Javier; Iannicelli, Jesica; Laino, Leandro Ezequiel; Burrieza, Hernan Pablo; Escandón, Alejandro Salvio; Pitta-Álvarez, Sandra Irene (Frontiers in Plant Science, 2019)
Ultraviolet-B radiation (UV-B, 280-320 nm) is an important environmental signal that regulates growth and development in plants. There are two dose-dependent UV-B response pathways in plants: a specific one, mediated by UVR8 (the specific UV-B receptor) and an unspecific one, which is activated by the oxidative damage produced by radiation. The receptor is constitutively expressed, and, in the presence of UV-B, induces the monomerization of the UVR8 dimer. The monomer then interacts with COP1, an ubiquitin ligase, hindering its ability to ubiquitine the transcriptional factor HY5, thus averting its degradation and activating the photomorphogenic response. HY5 induces the synthesis of proteins RUP1 and RUP2, which interact with UVR8, liberating COP1 and inducing dimerization of UVR8. This mechanism has been thoroughly characterized in Arabidopsis, and it has been demonstrated that the UVR8 receptor is key to the UV-B response. Although Arabidospis is the model plant, due to its characteristics and the wide variety of available mutants, many of the mechanisms described in Arabidopsis differ in other plants. In this paper, we review the latest information regarding UV-B response mediated by UVR8 in different species, focusing on the differences reported compared to Arabidopsis. For instance, UVR8 is not only induced by UV-B but also by other agents that are expressed differentially in diverse tissues. Also, in some of the species analyzed, proteins with low homology to RUP1 and RUP2 were detected. We also discuss how UVR8 is involved in other developmental and stress processes that are not UV-B dependent. We conclude that the receptor is highly versatile and that there is a differential response between Arabidopsis and other species.